INTEGRATING SHORT STORIES INTO LANGUAGE TEACHING TO ENHANCE VOCABULARY ACQUISITION (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Vocabulary acquisition plays a crucial role in second language learning, yet traditional vocabulary teaching methods often fail to provide sufficient contextual exposure. This study explores the integration of short stories into English language teaching as an effective strategy for enhancing learners’ vocabulary acquisition. The findings suggest that incorporating short stories into language instruction positively impacts learners’ vocabulary development and overall language proficiency.